IMPLEMENTATION OF EDUTAINMENT LEARNING METHOD ON THE USE OF HAND TOOLS TO IMPROVE THE LEARNING OUTCOMES OF VOCATIONAL HIGH SCHOOL STUDENTS - Firmansyah, Ferdy Aditya; Garnadi, Andi (Universitas Pendidikan Indonesia, 2024)
The purpose of this study is to determine the improvement in learning outcomes for students in terms of cognitive aspects and to understand the students' response and learning activities when using the Edutainment method. The study was conducted at SMK Negeri 2 Cimahi, in the 10th grade - TP B class, with 33 student participants. The instruments used were tests, questionnaires, and observations. The results of the study showed that students' learning outcomes improved significantly after using the Edutainment method, with a N-Gain score of 0.85 and a highly positive response in terms of learning activities and student engagement with the edutainment method.